Design and synthesis of new coumarin-1,2,3-triazole hybrids as new antidiabetic agents: In vitro α-amylase, α-glucosidase inhibition, anti-inflammatory, and docking study - Barangi, Vinayaka Chandrappa; Shastri, Lokesh Anand; Chowdegowda, Prakasha Kothathi; Sangappanavar, Rohini; Inamdar, Karthik; Dalbanjan, Nagarjuna Prakash; Barretto, Delicia Avilla; Sunagar, Vinay (European Journal of Chemistry, 2024)
The current study focuses on the synthesis of coumarin-triazole hybrids (7i-t) starting from 4-hydroxy benzaldehyde or 4-hydroxyacetophenone (1a-b) and propargyl bromide. On the other hand, coumarin derivatives (5c-h) were prepared by Pechmann cyclization and treated with sodium azide to give the corresponding 3-azido methyl coumarins (6c-h). Finally, 1,3-dipolar cycloaddition between compounds 6c-h and terminal alkyne 2a-b produces coumarin-triazole hybrids (7i-t) utilizing click chemistry approaches that are high yielding, wide in scope and simple to perform. The structural proofs of the newly synthesized coumarin-triazole hybrids (7i-t) are proved by various spectroscopic techniques, including IR, 1H NMR, 13C NMR, and LC-MS. The synthesized new coumarin triazole hybrids (7i-t) were explored for their antihyperglycemic potential and therefore evaluated for α-glucosidase and α-amylase inhibitory activities along with anti-inflammatory. The results suggest that among the series, compound 7l showed excellent activity with an IC50 value of 0.67±0.014 mg/mL and 0.72±0.012 mg/mL for α-amylase, and α-glucosidase inhibitory potential while compound 7o showed promising anti-inflammatory activity with IC50 value of 0.54±0.003 mg/mL. To support the above findings, molecular docking studies were performed, which confirmed the interaction of the synthesized molecules 7i-t with an effective binding energy of -9.0 to -10.6 kcal/mol at the active site of the enzyme human pancreatic α-amylase (PDB ID: 1B2Y). Therefore, these scaffolds have the potential to function as lead candidates for antidiabetic and anti-inflammatory activities.